2020
DOI: 10.3390/jcm9092700
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Impact of Polycystic Ovary Syndrome in Recurrent Miscarriage: A Retrospective Cohort Study and Meta-Analysis

Abstract: Background: The use of different definitions and diagnostic approaches of polycystic ovary syndrome (PCOS) and recurrent miscarriage (RM) has led to a wide range of prevalence rates in the literature. Despite the persistent controversy about the factual prevalence of PCOS in RM, a vast number of studies have revealed evidence about their association with each other. The goals of this study were to evaluate the prevalence of polycystic ovarian morphology and PCOS within the RM population, performing meta-analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…Furthermore, positive correlations were found between the number of miscarriages and OVol, 17-OHP, A4 and LH, suggesting that the women with PCOM and elevated adrenal androgens can be at a higher risk of miscarriages compared to the women with a previous diagnosis of PCOS but no features of PCOM or adrenal HA. Unless it has been proved that PCOS may independently from BMI increase the risk of miscarriage [ 50 , 90 , 91 ], the direct causes of this implication are poorly recognized. Several potential risk factors of miscarriages in PCOS have been described.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, positive correlations were found between the number of miscarriages and OVol, 17-OHP, A4 and LH, suggesting that the women with PCOM and elevated adrenal androgens can be at a higher risk of miscarriages compared to the women with a previous diagnosis of PCOS but no features of PCOM or adrenal HA. Unless it has been proved that PCOS may independently from BMI increase the risk of miscarriage [ 50 , 90 , 91 ], the direct causes of this implication are poorly recognized. Several potential risk factors of miscarriages in PCOS have been described.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we found that the prevalence of PCO was 18 (19.1%) with RM. Mayrhofer et al (4) found that PCOS was found in 43 (9.5%) of all women. Rai et al (8) found that the prevalence of polycystic ovarian morphology amongst women with recurrent miscarriage was 40.7% (895/2199).…”
Section: Discussionmentioning
confidence: 97%
“…Polycystic ovarian syndrome (PCOS) is a clinically and biochemically heterogeneous disorder. It is the most common endocrinopathy in reproductive aged women affecting 4%-12% (4) . Numerous studies have investigated the association between PCOS and RM.…”
Section: Introductionmentioning
confidence: 99%
“…Polycystic ovary syndrome (PCOS) is one of the most common endocrine disorders among women in their reproductive age and the prevalence of this syndrome varies from 6.5 to 19.9% in the world [ 1 , 2 ]. According to the latest systematic review studies, the prevalence of this syndrome is estimated at 3% according to the definition provided by the National Institutes of Health (NIH) and at 7% according to the definition provided by Rotterdam in Iran [ 3 ].…”
Section: Introductionmentioning
confidence: 99%